Effect of Methyl Jasmonate Treatment on Primary and Secondary Metabolites and Antioxidant Capacity of the Substrate and Hydroponically Grown Chinese Chives - Wang, Cheng; Zhang, Jing; Lv, Jian; Li, Jing; Gao, Yanqiang; Patience, Bakpa Emily; Niu, Tianhang; Yu, Jihua; Xie, Jianming (Frontiers in Nutrition, 2022)
Hydroponic culture has become a commercial planting model for leafy vegetables, herbs, and other plants with medicinal value. Methyl jasmonate (MeJA) is involved in primary and secondary plant metabolism; moreover, it regulates plant bioactive compounds and enhances the nutritional and medicinal value of plants. We performed targeted metabolomic analysis of the primary and secondary metabolites in substrate-grown and hydroponic Chinese chive leaves sprayed with MeJA (0 μM, 300 μM, 500 μM, and 800 μM). Using ultra-performance liquid chromatography (UPLC), UPLC tandem mass spectrometry, and chemometric tools, and analyzed the antioxidant activity of these plants. We identified the biomarkers of amino acids (serine, proline, lysine, and arginine) and phenolic compounds (4-coumaric acid and protocatechuic acid) using chemometric tools to distinguish between substrate-grown and hydroponic Chinese chives treated with MeJA. MeJA (500 μM) treatment significantly increased the total sugar and amino acid (essential and non-essential amino acids and sulfur-containing amino acids) contents of hydroponically grown Chinese chives. However, the changes in total sugar and amino acid contents in Chinese chive grown in substrates showed the opposite trend. The organic acid content of hydroponically grown Chinese chives treated with MeJA decreased significantly, whereas that of substrate-grown plants treated with 300 μM MeJA increased significantly. Further, MeJA treatment significantly increased the phenolic content of substrate-grown Chinese chives. Treatment with 800 μM MeJA significantly increased the carotenoid content of substrate-grown Chinese chives and the phenolic content of hydroponic Chinese chives. In addition, the 500 μM MeJA treatment significantly increased the antioxidant activity of Chinese chives in both substrate-grown and hydroponic cultures, and promoted the accumulation of nutrients and bioactive substances. This treatment also improved the flavor quality of these plants and their nutritional and medicinal value. Thus, the results suggested that MeJA-treated plants could be used as value-added horticultural products.